2009
DOI: 10.1029/2008jb006074
|View full text |Cite
|
Sign up to set email alerts
|

Kilauea slow slip events: Identification, source inversions, and relation to seismicity

Abstract: Several slow slip events beneath the south flank of Kilauea Volcano, Hawaii, have been inferred from transient displacements in daily GPS positions. To search for smaller events that may be close to the noise level in the GPS time series, we compare displacement fields on Kilauea's south flank with displacement patterns in previously identified slow slip events. Matching displacement patterns are found for several new candidate events, although displacements are much smaller than previously identified events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 74 publications
(182 reference statements)
7
81
2
Order By: Relevance
“…There are two sources for the dataset used in this study: source parameters inferred directly from the slip distributions of Schmidt and Gao (2010) for the Cascadia subduction zone and source parameters reported in the literature for other subduction zones (e.g., Obara et al, 2004;Brown et al, 2005;Douglas et al, 2005;Hirose and Obara, 2005;Wallace and Beavan, 2006;Ito and Obara, 2006;Hirose and Obara, 2006;CorreaMora et al, 2008CorreaMora et al, , 2009Hirose and Obara, 2010;Sekine et al, 2010; see references in Ⓔ Table S1, available in the electronic supplement to this paper). Additionally, we also include documented aseismic slip on the San Andreas fault (Linde et al, 1996) and Hawaii's south rift zone (Segall et al, 2006;Montgomery-Brown et al, 2009). In this study, we attempt to focus on a specific type of slow slip phenomenon in order to ensure that we are studying a consistent underlying process.…”
Section: Slow Slip Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two sources for the dataset used in this study: source parameters inferred directly from the slip distributions of Schmidt and Gao (2010) for the Cascadia subduction zone and source parameters reported in the literature for other subduction zones (e.g., Obara et al, 2004;Brown et al, 2005;Douglas et al, 2005;Hirose and Obara, 2005;Wallace and Beavan, 2006;Ito and Obara, 2006;Hirose and Obara, 2006;CorreaMora et al, 2008CorreaMora et al, , 2009Hirose and Obara, 2010;Sekine et al, 2010; see references in Ⓔ Table S1, available in the electronic supplement to this paper). Additionally, we also include documented aseismic slip on the San Andreas fault (Linde et al, 1996) and Hawaii's south rift zone (Segall et al, 2006;Montgomery-Brown et al, 2009). In this study, we attempt to focus on a specific type of slow slip phenomenon in order to ensure that we are studying a consistent underlying process.…”
Section: Slow Slip Data Setmentioning
confidence: 99%
“…Slow slip events, which represent the transient release of strain over the duration of days toweeks, occur downdip of the transition zone between the locked seismogenic zone and the free-slipping zone on the plate interface, and fluids are thought to be critical for its occurrence (e.g., Obara, 2002;Rogers and Dragert, 2003). Slow earthquakes have also been reported in other tectonic environments such as the San Andreas fault (Linde et al, 1996) and Hawaii (Segall et al, 2006;Montgomery-Brown et al, 2009). Although several hypotheses have been proposed to explain these events (e.g., Ito et al, 2007;Schwartz and Rokosky, 2007;Brodsky and Mori, 2007;Ide, 2008;Liu and Rice, 2009;Ando et al, 2010;Hawthorne and Rubin, 2010;Ide, 2010;Liu and Rubin, 2010;Peng and Gomberg, 2010;Shibazaki et al, 2010), the physical mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a reasonable assumption for the shallow dike, such a low value could lead to an underestimation of the depth of the deeper dike. Models with depthdependent elastic properties, with more compliant layers at shallow depth and stiffer layers at greater depth, always lead to over-estimations of source depths, whether these sources are shear faults [Arnadottir et al, 1991;Montgomery-Brown et al, 2009] or magmatic reservoirs [Masterlark, 2007].…”
Section: Bias Induced By the Homogeneous Elasticity Hypothesismentioning
confidence: 99%
“…Surface displacements during periods of unrest have been used to determine the geometries and volume changes of magma bodies [2,7,[19][20][21]. By modeling geodetic observations, previous studies have demonstrated that there are at least three or four discrete magma reservoirs beneath Kīlauea's summit.…”
Section: Introductionmentioning
confidence: 99%